Effect of Cu on the microstructures and properties of WC-6Co cemented carbides fabricated by SPS. (January 2017) - Huang, Zhu; Ren, Xingrun; Liu, Meixia; Xu, Chang; Zhang, Xuehui; Guo, Shengda; Chen, Hao
Abstract: The aim of this work is to study the effect of Cu on sintering temperature, densification, microstructure and mechanical properties of WC-6Co cemented carbides fabricated by spark plasma sintering (SPS). Fine grained WC powders with an average size of 1.2 μm, were investigated. Microstructures, hardness, fracture toughness and wear resistance of WC-6(Co/Cu) cemented carbides were measured and observed using SEM, mechanical property test. The results show that the sintering temperature of WC-6Co cemented carbides can be decreased obviously with Cu added; addition of Cu reduced grain size to 0.85 μm, but led to lower density. The adding amount of Cu should be controlled within a certain range, and the samples adding the appropriate proportion of Cu can obtain higher hardness and wear resistance. Highlights: Cu powders are added into WC-6Co cemented carbides for promoting the properties. SPS is used in this test as a newly developed sintering method. The adding amount of Cu should be strictly controlled within a certain range.